Handbook of the Life Course - Mortimer, Jeylan T.; Shanahan, Michael J. (Kluwer Academic Publishers, 2003)
The development of the life course as a field of study parallels in some respects another prominent subfield of sociology, social psychology. In his now-classic assessment, House (1977) observed that social psychology’s highly general and abstract concepts are well suited to elucidate a broad range of phenomena. As a result, however, social psychological theorizing and research had tended to “dissipate” across several academic disciplines and many applied areas of research. These circumstances presented a challenge to social psychologists in their efforts to maintain a core identity and to evaluate the development of their field. A similar situation may be said to characterize the contemporary literature surrounding the life course. As a concept, the life course refers to the age-graded, socially-embedded sequence of roles that connect the phases of life. As a paradigm, the life course refers to an imaginative framework comprised of a set of interrelated presuppositions, concepts, and methods that are used to study these age-graded, socially embedded roles. In this relatively new subfield of the social sciences, a common core of generalized concepts and premises is now taking hold and giving definite form to the life course paradigm. As with social psychology, the generalized nature of this paradigm has led to its diffusion across diverse problem areas. Indeed, the utility of the life course for the study of a wide range of temporally structured phenomena is clearly demonstrated by the contributions to this volume from leading specialists in their subfields. Further paralleling the circumstances of social psychology, academic infrastructures are not conducive to the recognition and development of life course studies as a field. Academic specializations, departments, professional societies, and scholarly journals all tend to promote a focus on single age groups or particular life phases (e.g., adolescence or old age). This emphasis is not in accord with the life course paradigm’s central premise—that no period of life can be understood in isolation from people’s prior experiences, as well as their aspirations for the future. Thus, whereas the life course has proven highly useful in the study of lives, it likewise tends toward the “organizationally challenged.”